2010
DOI: 10.1074/jbc.m110.104513
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of p400/mDomino Chromatin-remodeling ATPase in Bone Marrow Hematopoiesis and Cell-cycle Progression

Abstract: p400/mDomino is an ATP-dependent chromatin-remodeling protein that catalyzes the deposition of histone variant H2A.Z into nucleosomes to regulate gene expression. We previously showed that p400/mDomino is essential for embryonic development and primitive hematopoiesis. Here we generated a conditional knock-out mouse for the p400/mDomino gene and investigated the role of p400/mDomino in adult bone marrow hematopoiesis and in the cell-cycle progression of embryonic fibroblasts. The Mx1-Cre-mediated deletion of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…dom loss-of-function mutants display black melanotic masses that are composed of melanized lymph glands (Braun et al, 1997). Mutants have shown that the vertebrate homolog of dom is required for both embryonic and adult hematopoiesis in the laboratory mouse (Fujii et al, 2010;Ueda et al, 2007). Loss of a subunit of another ATP-dependent chromatin-remodeling complex, NURF, also causes melanotic masses (Badenhorst, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…dom loss-of-function mutants display black melanotic masses that are composed of melanized lymph glands (Braun et al, 1997). Mutants have shown that the vertebrate homolog of dom is required for both embryonic and adult hematopoiesis in the laboratory mouse (Fujii et al, 2010;Ueda et al, 2007). Loss of a subunit of another ATP-dependent chromatin-remodeling complex, NURF, also causes melanotic masses (Badenhorst, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested a role for Dom in prohemocyte survival. This function appears to have been conserved in mice, where a Dom homolog was shown to be important both in primitive hematopoiesis in the embryo and in the maintenance of hematopoietic progenitor cells in the adult bone marrow (Fujii et al, 2010;Ueda et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The SWR complex subunit P400 (EP400) has crucial functions during embryonic hematopoiesis (Fujii et al, 2010;Ueda et al, 2007). It regulates the expression of several embryonic globin genes and deregulates HOX gene expression.…”
Section: Developmental Roles Of Ino80/swr Complexesmentioning
confidence: 99%
“…It regulates the expression of several embryonic globin genes and deregulates HOX gene expression. In addition, the conditional deletion of P400 in bone marrow cells results in loss of the hematopoietic stem and progenitor cell pool due to defects in cell cycle progression (Fujii et al, 2010). Finally, INO80 is required for meiotic recombination during spermatogenesis (Serber et al, 2015).…”
Section: Developmental Roles Of Ino80/swr Complexesmentioning
confidence: 99%
“…The incorporation of H2A.Z in the body of genes is associated with active transcription and reduced DNA methylation (Conerly et al 2010). Inducible knockout of p400 results in impaired gene expression, including many MYC target genes (Fujii et al 2010). In addition, knockdown of another ATPase that interacts with MYC, ASH2/ANCCA, causes a reduction in MYC target gene activation (Ciro et al 2009).…”
Section: Chromatin Remodelingmentioning
confidence: 99%